2020
DOI: 10.3390/ma13132998
|View full text |Cite
|
Sign up to set email alerts
|

Investigations on Surface Roughness and Tool Wear Characteristics in Micro-Turning of Ti-6Al-4V Alloy

Abstract: Micro-turning is a micro-mechanical cutting method used to produce small diameter cylindrical parts. Since the diameter of the part is usually small, it may be a little difficult to improve the surface quality by a second operation, such as grinding. Therefore, it is important to obtain the good surface finish in micro turning process using the ideal cutting parameters. Here, the multi-objective optimization of micro-turning process parameters such as cutting speed, feed rate and depth of cut were perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(17 citation statements)
references
References 31 publications
0
16
0
1
Order By: Relevance
“…Finally, it is worth mentioning the employment of techniques based on the DOE and regression techniques that have also been widely used for the study of technological variables found in manufacturing processes as shown in research studies such as that of Airao et al [54] which analyzed the effect of cutting speed, feed rate, and axial depth of cut on surface roughness obtained in end-milling of a stainless steel, that of Kasdekara et al [55], which employed a 2 4 full factorial (DOE) for determining the most important factors which influence MRR in Electro-chemical machining of AA6061 by using MLP and regression, and that of Ahmed et al [56] in which the MRR, in laser milling of three alloys (Ti6Al4V, Inconel 718 and AA 2024), was evaluated using the response surface method and DOE. On the other hand, Aslantas et al [57] obtained empirical relations between cutting speed, feed rate, depth of cut and surface roughness parameters using the RSM for the micro-turning process in a Ti6Al4V alloy and Su et al [58] employed a multi-objective optimization method based on grey relational analysis and RSM along with Taguchi method for analyzing surface roughness and MRR in turning of an AISI 304 austenitic stainless steel. Regression analysis is also used by Zajac et al [59] to make predictions of cutting tool durability in turning processes.…”
Section: State Of the Artmentioning
confidence: 99%
“…Finally, it is worth mentioning the employment of techniques based on the DOE and regression techniques that have also been widely used for the study of technological variables found in manufacturing processes as shown in research studies such as that of Airao et al [54] which analyzed the effect of cutting speed, feed rate, and axial depth of cut on surface roughness obtained in end-milling of a stainless steel, that of Kasdekara et al [55], which employed a 2 4 full factorial (DOE) for determining the most important factors which influence MRR in Electro-chemical machining of AA6061 by using MLP and regression, and that of Ahmed et al [56] in which the MRR, in laser milling of three alloys (Ti6Al4V, Inconel 718 and AA 2024), was evaluated using the response surface method and DOE. On the other hand, Aslantas et al [57] obtained empirical relations between cutting speed, feed rate, depth of cut and surface roughness parameters using the RSM for the micro-turning process in a Ti6Al4V alloy and Su et al [58] employed a multi-objective optimization method based on grey relational analysis and RSM along with Taguchi method for analyzing surface roughness and MRR in turning of an AISI 304 austenitic stainless steel. Regression analysis is also used by Zajac et al [59] to make predictions of cutting tool durability in turning processes.…”
Section: State Of the Artmentioning
confidence: 99%
“…a) & (b) repersent the normal probalility curve for toughness and hardness and this plot is used to check the adquancy of model. as all points are in a straight line,it can concluded that model is adequate[16][17][18].…”
mentioning
confidence: 92%
“…The best surface with regard to roughness was reached at 150 m/min cutting speed and feed rate of 0.25 mm/rev. Machining of other steels, like the AISI 1040, was studied using "response surface methodology" (RSM) to find that tool wear and total machining time influence the surface roughness [20][21][22].…”
Section: Introductionmentioning
confidence: 99%